Aleksei Balabanov : Brother - Österberg, Ira (KinoSputnik, 2022)
"KinoSputniks closely analyse some key films from the history of Russian and Soviet cinema. Written by international experts in the field, they are intended for film enthusiasts and students, combining scholarship with an accessible style of writing. Ira Österberg's KinoSputnik on Aleksei Balabanov's cult film Brother (1997) examines the production history, context and reception of the film, and offers a detailed reading of its key themes. Balabanov's Brother made a mark on the new Russia's film history as its hero Danila Bagrov quickly gained cult status and the nostalgic rock soundtrack hit the nerve of the young post-Soviet generation. This study unravels the film's effective and ingenious mixture of genre elements, art narration and almost documentary-style realism, which would become trademarks for Balabanov's oeuvre. Primary readership will be among film studies students and film enthusiasts, but will also be of interest to anyone researching or studying film soundtracking. A list of all books in the series is here on the Intellect website on the series page KinoSputnik"--